Research on the influence of the soil tillage system on soybean yield at ards Turda - Alina Şimon; Felicia Cheţan; Cornel Cheţan; Valeria Deac (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The purpose of this paper is to evaluate the soybean yield obtained from the application of the minimum tillage system compared to the classical tillage system. Conservative tillage systems have become an important part of agriculture, and the need to apply these systems is justified by the growing area of land degraded by the erosion process. Experimental factors: Factor A - the tillage system: classical tillage system and minimum tillage system (chisel variant); Factor B - soybean varieties: Onix, Felix, Mæalina TD and Darina TD; Factor C - experimental years: 2015 and 2016. Following the application of the conservative tillage system, there is a slight decrease in yield compared to the classical tillage system, and between the two years studied, in 2016 there are yields with significantly higher differences compared to 2015. The application of conservative tillage systems brings important long-term benefits to both the soil and the environment by reducing soil compaction and fossil fuels used in crop technology.
Keywords: Q01; Q15; Q16; 330; climatic condition; soybean; tillage systems; yield